Świadectwo Boga Ojca o Jezusie w Ewangelii wg św. Jana - Kręcidło, Janusz (Verbum Vitae, 2015)
The article addresses the issue of the witness of the Father about Jesus in the Fourth Gospel. The topic is inscribed in the very essential theological message of the Gospel of John, according to which Jesus is the Messiah and the Son of God revealing the Father to the world. In two units of the Fourth Gospel (5:1-47 and 8:12-20) Jesus invokes the witness of the Father in order to prove his divine status. In the first passage Jesus argues that the witness of the Father about him is expressed by the witness of the people (John the Baptist), by Jesus’ works, and by the Scriptures. In the second passage he claims that the Father’s witness authenticates his divine origins, and that thanks to his status as the Son of God he is not subject to human judgment. In a third passage (12:20-36) examined in the article the voice of the Father coming from heaven gives the explicit witness confirming Jesus’ divine status and mission. The motif of the witness of the Father is strictly connected here with with the theme of the salvific activity of Jesus in the world as a means of increasing the glory of God.